The Influence of Promotion Through Instagram Social Media and E-WOM on Purchase Interest in UMKM Siris Meals Jakarta - Priatna, Gustinanda; Zaini, Achmad (CV. Proaksara Global Transeduka, 2025)
The rise of social media has transformed digital marketing strategies, with Instagram emerging as a key platform for small and medium-sized enterprises (MSME) to engage consumers. This study examines the impact of Instagram-based promotions and electronic word-of-mouth (E-WOM) on consumer purchase interest in Siris Meals Jakarta. A quantitative research approach was employed, utilizing a purposive sampling technique with a sample of 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that both Instagram promotions and E-WOM have a significant positive influence on purchase interest, both individually and collectively. The independent variables contributed 56.6% to variations in purchase interest. These results highlight the importance of optimizing Instagram as a promotional tool to enhance consumer engagement and drive sales. Based on these findings, it is recommended that Siris Meals strengthen its Instagram marketing strategy to maximize consumer reach and engagement